Improved pulse schemes for separated local field spectroscopy for static and spinning samples - Das, Bibhuti B.; Ajithkumar, Thalasseril G.; Ramanathan, K. V. (Solid State Nuclear Magnetic Resonance, 2008)
An improved pulse sequence for SLF experiments based on the magic sandwich (MS) scheme for homonuclear dipolar decoupling is proposed. The sequence incorporates a double MS, both on I and S spins and has been named as EXE-MS2. The proposed scheme which has a scaling factor of 1 is observed to be free from low intensity artifacts and provides better line-widths particularly for S spins labeled at multiple sites. The pulse sequence which has been applied on static oriented samples incorporates the EXE scheme where direct polarization of the S spin in the B-0 field is utilized in the place of polarization inversion and is observed to perform well without any loss of sensitivity while ensuring considerable reduction in rf power input into the sample. The EXE scheme has also been tested for solid samples under MAS. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: magic sandwich pulses; PISEMA; SLF